Synthesis and reactivity of [18F]-N-fluorobenzenesulfonimide. - Teare, H; Robins, E; Arstad, E; Luthra, S; Gouverneur, V (2007)
A novel [18F]NF reagent and two novel radiochemical transformations have been developed: [18F]NFSi has been prepared from sodium dibenzenesulfonimide and reacted in the presence of silyl enol ethers and allylsilanes to deliver labelled fluorinated ketones and allylic fluorides respectively; the radiosynthesis of the fluorinated A ring of vitamin D3 has also been completed with success.